Levels of antioxidant enzymes and alkaline protease from pulp and peel of sunflower - Mehdi, Wesen Adel; Yusof, Faridah; Farhan, Layla Othman; Mehde, Atheer Awad; Ahmad Raus, Raha (Elsevier BV, 2017)
Objective: The activity of enzymes participating in the systems of antioxidant protection was assayed in the peel and pulp of sunflower. The essential roles of proteases in food stimulate research to find other sources of the enzyme especially from non-conventional sources. In the present work, we study several biochemical parameters in the pulp and peel of sunflower. Methods: Pulp and peel of sunflower was extracted, antioxidant enzymes and nonenzymatic antioxidant were measured. Alkaline protease was measured and purified from pulp in sunflower. Results: High carbohydrate concentration, beta-carotene, catalase and ascorbate peroxidase activities, free radical scavenging capacity and free flavonoid content were observed in the peel of sunflower. Whereas, MDA and ceruloplasmin activities were high in the pulp of sunflower. Conclusions: The present study concluded that peel in sunflower are strong radical scavengers and can be considered as good sources of natural antioxidants for medicinal and commercial uses. Further analysis showed that protease activity was a significantly high in the pulp compared to the peel.